Turkish Berlin : Integration Policy and Urban Space - Hinze, Annika Marlen (Book collections on Project MUSE., 2013)
Turkish Berlin reveals how integration has been experienced by second-generation Turkish immigrant women in two neighborhoods in Berlin, Germany. Informed by first-person interviews with public officials and immigrants, Annika Marlen Hinze makes clear that local integration policies-often created by officials who have little or no contact with immigrants-have significant effects on the assimilation of outsiders into a community.